Carcinoma in a Thyroglossal Duct Cyst - Neupane, Y; Paudel, Dhundi Raj (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 24-26 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8186